From Subprime and Eurozone Crisis with Full Speed into the Next Financial Crisis - Strašek, Sebastjan (Naše gospodarstvo/Our economy, 2017)
This paper offers an analysis of the road from subprime and eurozone crisis to the elements of a new systemic crisis. Our aim is to research common issues that accompany each of these crises and to explore elements that hint that the financial systems are moving toward a new crisis. By holding short-term interest rates near zero, the central banks have encouraged malinvestment and speculation. Fuelling the bubble is the fear of missing out on trade. We find that actual events and movements on security markets follow a typical pattern, which indicates a serious threat for the next financial crisis. We also find enough signs that old crises lessons haven’t been learned.